Dual tissue-specific expression of apo-AII is directed by an upstream enhancer. - Shelley, C S (1987)
Apolipoprotein-AII (apo-AII) is one of a family of evolutionarily related proteins which play a crucial role in lipid transport and metabolism. The serum levels of human apo-AII have been shown to be inversely correlated to the incidence of coronary heart disease and its expression to be limited to the liver and intestine. Here we demonstrate that this dual tissue-specificity involves DNA sequences located in a 259 bp region centred 782 bp upstream from the transcription initiation site. These sequences function in an orientation-independent manner and are absolutely required for transcription from the apo-AII promoter. The regulatory region contains sequences which are homologous to the apo-AI, beta-globin and immunoglobulin gene promoters and to the immunoglobulin heavy-chain enhancer.